Greenhouse gas balance and carbon footprint of beef cattle in three contrasting pasture-management systems in Brazil. (20th January 2017) - de Figueiredo, Eduardo Barretto; Jayasundara, Susantha; de Oliveira Bordonal, Ricardo; Berchielli, Telma Teresinha; Reis, Ricardo Andrade; Wagner-Riddle, Claudia; La Scala Jr., Newton
Abstract: Integrated Systems (IS) have been identified as an efficient land-management strategy for restoring degraded areas worldwide, increasing crops and beef yields and providing technical potential for carbon (C) sequestration in soil and trees as an option for offsetting CH4 and N2 O emissions from cattle production. The aim of our study is to estimate the greenhouse gas (GHG) balance and the C footprint of beef cattle (fattening cycle) in three contrasting production scenarios on the Brachiaria pasture in Brazil—1) degraded pasture (DP), 2) managed pasture (MP), and 3) the crop-livestock-forest integrated system (CLFIS)—presenting new alternatives of land use as a GHG mitigation strategy. Area-scaled total GHG emissions were highest in MP (84, 541 kg CO2 eq ha −1 ), followed by CLFIS (64, 519 kg CO2 eq ha −1 ) and DP (8004 kg CO2 eq ha −1 ) over a 10-yr period. Our results note that the highest C footprint of beef cattle was in the DP, 18.5 kg CO2 eq per kg LW (live weight), followed by 12.6 kg CO2 eq per kg LW in the CLFIS and 9.4 kg CO2 eq per kg LW in the MP, without taking into account the technical potential for C sequestration in MP (soil C) and CLFIS (soil and Eucalyptus C). Considering the potential for soil C sequestration in the MP and CLFIS, the C footprint of beef cattle could be reduced to 7.6 and −28.1 kg CO2 eq per kg LW in the MP and CLFIS, respectively. The conversion of the degraded pasture to a well-managed pasture and the introduction of CLFIS can reduce their associated GHG emissions in terms of kg CO2 eq emitted per kg of cattle LW produced, increasing the production of meat, grains and timber. This reduction is primarily due to pasture improvement and increases in cattle yields and the provision of technical potential for C sinks in soil and biomass to offset cattle-related emissions. Graphical abstract: Greenhouse gas emissions (×10 3 kg CO2 eq ha −1 ) per source (right bars) and potential for C sink (left bars) accumulated over a 10-year period for each pasture management system: Degraded Pasture (DP), Managed Pasture (MP) and Crop-Livestock-Forest-Integration System (CLFIS) in Brazil. Highlights: The recovery of degraded pastures can increase cattle and agricultural yields. Managed pasture and integration systems present high potential for C sink. Better pasture management practices can reduce cattle C footprint. Crop-livestock-forest integration systems can offset cattle emissions.